The reference epigenome and regulatory chromatin landscape of chronic lymphocytic leukemia. (June 2018) - Beekman, Renée; Chapaprieta, Vicente; Russiñol, Núria; Vilarrasa-Blasi, Roser; Verdaguer-Dot, Núria; Martens, Joost; Duran-Ferrer, Martí; Kulis, Marta; Serra, François; Javierre, Biola; Wingett, Steven; Clot, Guillem; et al.
Abstract Chronic lymphocytic leukemia (CLL) is a frequent hematological neoplasm in which underlying epigenetic alterations are only partially understood. Here, we analyze the reference epigenome of seven primary CLLs and the regulatory chromatin landscape of 107 primary cases in the context of normal B cell differentiation. We identify that the CLL chromatin landscape is largely influenced by distinct dynamics during normal B cell maturation. Beyond this, we define extensive catalogues of regulatory elements de novo reprogrammed in CLL as a whole and in its major clinico-biological subtypes classified by IGHV somatic hypermutation levels. We uncover that IGHV-unmutated CLLs harbor more active and open chromatin than IGHV-mutated cases. Furthermore, we show that de novo active regions in CLL are enriched for NFAT, FOX and TCF/LEF transcription factor family binding sites. Although most genetic alterations are not associated with consistent epigenetic profiles, CLLs withMYD88 mutations and trisomy 12 show distinct chromatin configurations. Furthermore, we observe that non-coding mutations in IGHV-mutated CLLs are enriched in H3K27ac-associated regulatory elements outside accessible chromatin. Overall, this study provides an integrative portrait of the CLL epigenome, identifies extensive networks of altered regulatory elements and sheds light on the relationship between the genetic and epigenetic architecture of the disease. An integrated resource of (epi)genomic features in annotated chronic lymphocytic leukemia (CLL) primary samples uncovers subgroup-specific regulatory alterations associated with clinical behavior.